INTEGRASI NILAI-NILAI QUR’ANI DALAM SISTEM EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMAN 1 MAKARTI JAYA - Ari Koswara; Fitria Hartati; Alimron; Suharmon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe how Qur’anic values are integrated into the evaluation system of Islamic Religious Education (PAI) learning at SMAN 1 Makarti Jaya. Evaluation in the Islamic perspective does not merely assess students’ cognitive achievements but also encompasses affective and spiritual dimensions grounded in Qur’anic values such as justice (al-‘adl), responsibility (al-hisab), balance (al-wazn), and honesty (ash-shidq). The research employed a qualitative descriptive method with a field study approach. Data were collected through interviews with PAI teachers, classroom observations, and analysis of assessment documents. The findings reveal that PAI teachers at SMAN 1 Makarti Jaya have implemented Qur’anic-based evaluation principles through a continuous, fair, and character-oriented assessment system, which includes initial, formative, and summative evaluations. This implementation aligns with the values of tazkiyah an-nafs (self-purification) and hisab (accountability), indicating that evaluation functions not only as a measure of learning outcomes but also as a means of moral development. The study recommends strengthening teacher training programs to design evaluation instruments systematically based on Qur’anic values to enhance the spiritual and moral dimensions of education.